Ultralow Thermal Conductivity of Single‐Crystalline Porous Silicon Nanowires. (25th August 2017) - Zhao, Yunshan; Yang, Lina; Kong, Lingyu; Nai, Mui Hoon; Liu, Dan; Wu, Jing; Liu, Yi; Chiam, Sing Yang; Chim, Wai Kin; Lim, Chwee Teck; Li, Baowen; Thong, John T. L.; et al.
Abstract: Porous materials provide a large surface‐to‐volume ratio, thereby providing a knob to alter fundamental properties in unprecedented ways. In thermal transport, porous nanomaterials can reduce thermal conductivity by not only enhancing phonon scattering from the boundaries of the pores and therefore decreasing the phonon mean free path, but also by reducing the phonon group velocity. Herein, a structure–property relationship is established by measuring the porosity and thermal conductivity of individual electrolessly etched single‐crystalline silicon nanowires using a novel electron‐beam heating technique. Such porous silicon nanowires exhibit extremely low diffusive thermal conductivity (as low as 0.33 W m −1 K −1 at 300 K for 43% porosity), even lower than that of amorphous silicon. The origin of such ultralow thermal conductivity is understood as a reduction in the phonon group velocity, experimentally verified by measuring the Young's modulus, as well as the smallest structural size ever reported in crystalline silicon (<5 nm). Molecular dynamics simulations support the observation of a drastic reduction in thermal conductivity of silicon nanowires as a function of porosity. Such porous materials provide an intriguing platform to tune phonon transport, which can be useful in the design of functional materials toward electronics and nanoelectromechanical systems. Abstract : Ultralow thermal conductivity of single‐crystalline porous silicon nanowires is probed. An electron‐beam technique is employed to directly measure the porosity of individual nanowires and also measure their thermal conductivity. A classical size effect due to small structure size combined with phonon softening arising from a large surface‐to‐volume ratio is shown to explain this behavior within the framework of diffusive thermal transport.